Peritoneal encapsulation: a preoperative diagnosis is possible. Issue 913 (1st November 2001) - Naraynsingh, V; Maharaj, D; Singh, M; Ramdass, M J
Abstract : Peritoneal encapsulation is an exceedingly rare developmental abnormality in which the small intestine is encased in an accessory peritoneal sac between the omentum and mesocolon. Two clinical signs associated with the dense fibrous layer encapsulating the intestine are described. The first is a fixed, asymmetrical distension of the abdomen, which does not vary with peristaltic activity due to the unvarying position of the fibrous capsule. The second is the difference in the consistency of the abdominal wall to palpation. The flat area is firm, due to the dense fibrous capsule and the distended area soft, due to the thin walled distended small intestine with no overlying fibrous layer.